Economia criativa: impacto do Festival Folclórico de Parintins na economia parintinense entre 2005 – 2019 - Lima, Larissa Thaináh Góes (Brasil, 2025)
The present research aimed to evaluate the financial impact of the Parintins Folklore Festival on the economy of Parintins through its economic activities, considering the period from 2005 to 2019. To achieve this goal, the following specific objectives were established: a) to analyze the performance of the Parintins economy through its municipal GDP and compare it to the GDP of Amazonas State; b) to examine the cultural sector expenditures in Parintins and contrast them with the state government’s financial transfers; c) to conduct a statistical survey of the financial flow generated by the Parintins Folkloric Festival. It consists of being a quantitative research with a descriptive objective, using data extracted from official Brazilian and Amazonian government websites, such as the Gross Domestic Product (GDP) and the financial movement of tourists during the festival period. The results indicated that the services sector holds a significant weight in the municipal GDP, as it does in the state GDP. Furthermore, the financial movement generated by the festival was found to have a substantial influence on the GDP of Parintins.